DETERMINAN FAKTOR STRUKTUR MODAL STUDY PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Dody Salden Chandra (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
This study aims to determine and analyze the Determinants of Capital Structure Factors. In this study, the capital structure will be tested by looking at its effect through firm value, total asset turnover, and current ratio in automotive companies listed on the BEI. The approach used in this study is an associative approach. The research population was 13 companies and samples that met the criteria (purposive sampling) in the sampling for the study were 7 companies. observations made for 5 years starting from 2013-2017. The data analysis technique used in this study is multiple linear regression analysis, which was carried out before testing the classical assumptions, and continued with the t test, F test and the coefficient of determination. This research data processing using SPSS statistical software. Partially, the value of the company has no significant effect on the capital structure. Partially the total asset turnover has a partial effect on the capital structure. And partially the current ratio has a significant effect on capital capital structure